Bioactivity of Papua Red Fruit Extract (Pandanus conoideus L.) Against Superoxide dismutase, Malondialdehyde and Blood Glucose of Rat (Rattus norvegicus L.) Hyperglycemia - Mokosuli, Yermia Semuel; Migau, Natalina; Wurarah, Masje (Molekul, 2024)
Red fruit (Pandanus conodus L.) is a plant native to Papua, ethnomedical used as a traditional medicine with a wide spectrum of pharmacological effects. However, research on the bioactivity of red fruit is still very poorly reported. The aim of this study was to characterize the bioactive content, antioxidant bioactivity and the effect of lowering blood glucose in hyperglycemic rats. Red fruit has extracted used the maceration method with 95% ethanol. Analysis of active compound content using Gas Chromatography Mass Spectrophotometry (GC MS). Analysis of Malondialdehyde (MDA), Superoxide dismutase (SOD) and blood glucose levels was carried out using the in vivo method using white rats. The research results showed that red fruit ethanol extract contained 173 compounds from six main groups of compounds. Red fruit extract has effective in reducing MDA levels in hyperglycemic mice. K4 and K5 treatments were the best treatments for reducing MDA. Red fruit extract affects the duration of induction of increased SOD in hyperglycemic rats. Treatments K4 and K5 were the best treatments for SOD induction. Red fruit extract affects reducing blood glucose in hyperglycemic mice. Red fruit extract has antioxidant activity and lowers blood glucose. Red fruit extract has the potential to be developed as a source of bioactive antioxidants and antidiabetics. Keywords: Glucose, hyperglycemia, malondialdehyde, superoxide dismutase